Group trauma focused cognitive behavior therapy for parents of premature infants compared to individual therapy intervention. (June 2023) - Shaw, Richard J.; Moreyra, Angelica; Simon, Stephanie; Wharton, Emily; Dowtin, LaTrice L.; Armer, Erin; Goldman, Lindsey Wallace; Borkovi, Tonyanna; Neri, Eric; Jo, Booil; Hintz, Susan; Van Meurs, Krisa; et al.
Abstract: Background: The current study compares results of a group-based intervention developed to reduce symptoms of posttraumatic stress, depression, and anxiety in parents of premature infants with a prior study using an individual version of the treatment manual. Methods: 26 mothers of preterm infants (25–34 weeks' gestational age; >600 g) received 6 sessions of trauma-focused cognitive behavior therapy (CBT). Outcomes were compared with those of a previously published RCT, which tested an individual therapy based on the same model in a group of 62 mothers. Results were also compared across in-person and telehealth treatment. Results: From baseline to follow up, the individual intervention showed greater improvement in trauma symptoms assessed with the Davidson Trauma Scale (d = 0.48, p = 0.016), although both conditions showed clinically significant improvement. Similar patterns were found for maternal depression and anxiety. In-person treatment was found to be superior to telehealth treatment administered during the COVID-19 pandemic, although the difference was not significant. Conclusions: Group-based trauma focused CBT is an effective treatment modality for parents of premature infants with symptoms of psychological distress but not as effective as individual therapy using the same treatment model. Highlights: Group therapy using trauma focused CBT is an effective intervention to reduce symptoms of psychological distress in parents of premature infants. Group therapy is less effective than an individual psychotherapy version of the same treatment. Treatment provided by telehealth is comparable to treatment provided in person.